From the lowlands to the highlands of Ecuador, a study of the genus Masteria (Araneae, Mygalomorphae, Dipluridae) with description of seven new species - Dupérré, Nadine; Tapia, Elicio; Quandt, Dietmar; Crespo-Pérez, Verónica; Harms, Danilo (Zootaxa, 2021)
Dipluridae represent a small Mygalomorphae family of South American origin, the family includes two subfamilies Diplurinae and Masteriinae although the placement of the latter in Dipluridae is still under debate. The family has a predominantly South American distribution although the genus Masteria L. Koch, 1873 presents an interesting distribution with representatives found in Fiji, Micronesia, New Caledonia, New Guinea and Australia. This genus is diverse at the species level in tropical South America and the Caribbean but no species have been described from Ecuador to date. Ongoing field work as part of the BIO-GEEC Project—a consortium established by several Ecuadorian and German institutions—has resulted in the discovery of several new species from both lowlands and highland habitats in Ecuador. Herein we described seven new species of Masteria from Ecuador: M. jatunsacha n. sp. (male); M. machay n. sp. (female); M. chalupas n. sp. (male); M. papallacta n. sp. (male and female); M. pasochoa n. sp. (male and female); M. lasdamas n. sp. (male); and M. otongachi n. sp. (male). The type species of the genus, Masteria hirsuta L. Koch, 1873 from Fiji, is redescribed and re-illustrated, from the original type specimen.